THE METHODS OF LITERARY WORKS OF SCOTT FITZGERALD - Tukhtaeva Nargiskhan Isomiddinovna; Amirova Marvarid Khamidullo qizi; Tursunova Oydinoy Dilshodbek qizi (Galaxy International Interdisciplinary Research Journal, 2022)
These feeling of the writer, on his words, were not "beliefs of the revolutionary, but only slowly smoulderring hate peasant"1, but they were so strong that have painted itself majority of his product, having done critical scene of the world "the Great" one of the main that his creative activity. And his final condemnation to this lifes always could be extremely severe and pitiless, and such condemnation particularly has obviously sounded in novel "The Gentle Night".Fitzgerald has somehow noticed "personality I interest only In her relations with society".